O manifesto literário como ação de linguagem : uma proposta de didatização do gênero para a leitura em sala de aula - Santos, Evandro Oliveira (2018)
The present research is based on the assumption that portuguese language teaching should focus on students' language skills development, based on the work of the text genres. Our problematic concerns the difficulties of students to adequately carry out the reading of texts in the discursive-enunciative plane. Its purpose is to enable the appropriation of the linguistic practices associated with the reading of the genre manifest literary. As a model of analysis, we use the theoretical-epistemological perspective defended by researchers at the University of Geneva, identified with sociodiscursive interactionism (SDI), especially the postulates of Bronckart (2009), which are associated with three central bases: social interactionism of Vygotsky (2008), the science of the text-speech of Bakhtin (2003) and Volochinov (2013) and Saussurian Linguistics (2006). Based on an action research based on Thiollent (2012), in a context of public elementary school in the city of Paripiranga-BA, we developed a teaching intervention that followed the principle of the didactic transposition of gender, with the adoption of the Didactic Reading Sequence (DRS), adapted from Dolz, Noverraz & Schneuwly (2004) to interpret the language action to manifest itself from a corpus composed by Manifestos of Manifests from poetry redwood (1924) and Anthropophagus (1928), written by Oswald Andrade and Manifest of Peripheral Anthropophagy (2007), written by Sérgio Vaz. This is an important contribution to linguistic studies, in that it seeks to overcome deficiencies in the domain of genres that are difficult for students to access, as well as to make an approach derived from applied linguistics for texts that are generally read as introductory to literary studies. In general, the DRL procedure proved to be a good instrument for the mediation of learning based on new conceptions of teaching focusing on language practices. As a result, therefore, we developed a Teaching Product of Gender (TPG), through the elaboration of an activity book for the reading of the literary manifest in the classroom, in order to contribute to the teaching practices that are associated with a sociodiscursive.